ANALISIS PENILAIAN TINGKAT KESEHATAN BANK BERDASARKAN METODE CAMEL PADA PT BANK MANDIRI (PERSERO) TBK TAHUN 2018-2022 - Adia Ningsih, Rizky; Lisdawati (Journal of Research and Publication Innovation, 2024)
This research aims to determine financial performance and to determine and analyze the health level of PT Bank Mandiri (Persero) TBK. The analysis tool used is CAMEL. Assessment using the CAMEL method consists of CAR, ROA, BOPO and LDR. This research uses quantitative data with descriptive research using secondary data. The results of this research indicate that the level of bank health at PT. Bank Mandiri (Persero) TBK is measured by financial performance. Capital is measured using the CAR ratio in 2018 of (1,209.6), in 2019 of (1,213.9), in 2020 of (1,199), in 2021 of (1,196), in 2022 of (1,194.6) categorized in the no group healthy, Earnings are measured using the ROA ratio in 2018 of (1433.33), in 2019 of (1440), in 2020 of (793.33), in 2021 of (1180), in 2022 of (1506.66) categorized in healthy and BOPO group in 2018 amounted to (49.86), in 2019 amounted to (51.93), in 2020 amounted to (72.47), in 2021 amounted to (79.23), in 2022 amounted to (80.93) categorized as not healthy and liquidity is measured using the LDR ratio in 2018 of (75.12), in 2019 of (75.2), in 2020 of (128), in 2021 of (141.28), in 2022 of (151.36) categorized in healthy and unhealthy groups.